IT Management Dengan K-Means Clustering Untuk Pengelompokkan Stok Barang - Kurnia, Nensi; Muhammad, Abulwafa; Yanto, Heri (Riset Sinergi Indonesia (RISINDO), 2023)
Management of transaction data in the retail business under study is still carried out conventionally and has not been integrated, this causes the complexity of calculating the number of transactions and stock of goods. For this reason, an analysis of sales transactions was carried out using the k-means method using sales transaction data for 24 samples of goods. There are 3 clusters formed with iteration calculations carried out in 4 iteration stages. The first cluster (Selling Goods) produced 7 items, the second cluster (Selling Goods) produced 5 items and the third cluster (Unsold Goods) produced 12 members. The results of this clustering analysis are used to implement business IT applications in retail business transactions.